Peran Pendidikan Agama Islam dalam Membangun Pluralisme - Dinda Wulandari; Nusyaibah; Fawati Titi Suyana; Ahmad Izzudin (Halaqatuna, 2026)
Indonesia is a country rich in cultural, religious, and ethnic diversity, with more than 300 ethnic groups and hundreds of regional languages. This diversity demands the implementation of inclusive Islamic education to foster harmonious and tolerant pluralism. This study employs a qualitative approach through a literature review method to explore the role of Islamic religious education in promoting tolerance and pluralism from the perspective of the Al-Qur'an. The findings reveal that Islamic religious education can serve as an effective agent of social transformation when implemented with inclusive, moderate values based on the principle of rahmatan lil ‘alamin. Inclusive Islamic education successfully instills values of mutual respect and eliminates discrimination, thereby facilitating harmonious relationships between Muslims and non-Muslims in Indonesia. The major challenges arise from political polarization, stereotypes, and structural educational barriers that need to be addressed through curriculum strengthening and teacher training. The implications of this study emphasize the urgency of developing inclusive teaching methods and utilizing social media as an effective strategy for tolerance education in the digital era.